Peran Konsep Diri dalam Membentuk Interaksi Sosial Siswa di Sekolah - Mujahidah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
This research aims to determine and analyze the role of self-concept in shaping students’ social interactions at school. Self-concept is an important psychological factor that influences individual behavior in social interactions. In an educational context, students with a positive self-concept tend to have better social interaction skills. This research is library research through literature review and theoretical analysis, and the results of this research are that students’ self-concept plays a very important role in shaping each individual’s interactions. By forming a positive self-concept, students are able to behave assertively, are able to adapt in groups and have high empathy.